Tech-Supported Strategic Management, Digital Leadership, and Play-Based Interactive Learning: A Multilevel Survey of Quality Improvement in Early Childhood Education - Syarifudin, Aip; Muttaqin, Muhammad Azhar (International Journal of Educational Qualitative Quantitative Research, 2025)
The digital revolution has reshaped education worldwide, and early childhood education (ECE) is no exception, requiring institutions to integrate technology into management and leadership while maintaining play-based and developmentally appropriate practices. This study investigated the effects of tech-supported strategic management (TSM), digital leadership (DL), and play-based interactive learning (PBIL) on quality improvement (QI) in ECE, considering screen-time governance (STG) as a moderator and teacher digital preparedness for planning (TDPP) as a mediator. A quantitative multilevel survey was conducted with 290 principals and teachers from Indonesia and Malaysia. Data were collected through structured questionnaires and analyzed using multiple regression with SPSS, including moderation, mediation, and predictive modeling. Results showed that TSM, DL, and PBIL significantly influenced QI, with PBIL emerging as the strongest predictor. STG strengthened the effects of TSM, DL, and PBIL on QI, while TDPP mediated the relationship between these variables and QI. Predictive analysis further revealed that increasing TSM, DL, and PBIL simultaneously enhanced QI, whereas a decline in these variables led to a reduction in quality. These findings emphasize that technology in ECE should act as an enabler of management and leadership rather than as the primary medium for children’s learning. Theoretically, the study extends integrative models of digital management, digital leadership, and play-based pedagogy within ECE. Practically, it offers guidance for policymakers, school leaders, and teachers in designing quality improvement strategies that are digitally supported yet age-appropriate, highlighting play, interaction, and strict governance of screen time.